A Comparative Study of Physical and Chemical Parameters in Sistan and Baluchistan University Wastewater and Its Re-Use of Wastewater (International Journal of Sustainable Energy and Environmental Research, 2012)
Following the university’s needs and current draughts, the university decided to establish a waste water treatment plant for proper management of its exotic waters. The recycled water of the plant is used for irrigation of its green space as well as providing water for its garden plants through drip irrigation method. The tests were performed during a 6- month period using input- output measuring devices. These tests were according to standard methods book. The photometer, spectrophotometer, and atomic absorption machines were applied for measuring cations and anions and heavy metals, respectively. The test results were analyzed by EXCEL/SPSS software. Finally, the acquired data were compared with the standards of EPA and FAO’s and it was concluded that they are in accordance with these standards and proper for irrigation of the green space and the greenhouse products.